1999
DOI: 10.2307/3802500
|View full text |Cite
|
Sign up to set email alerts
|

Land-Use Patterns Surrounding Greater Prairie-Chicken Leks in Northwestern Minnesota

Abstract: To better manage wildlife populations, managers must know which combination of land uses creates optimal habitat. We used spatial analysis at a landscape scale to describe land-use patterns and patch characteristics surrounding leks of greater prairie-chicken (Tympanuchus cupido pinnatus L.) in the Agassiz Beach Ridges (ABR) landscape (2,467 km2) in northwest Minnesota. We hypothesized that types and patterns of land use favorable to greater prairie-chickens would be associated positively with lek versus non-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
42
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 15 publications
8
42
0
1
Order By: Relevance
“…The probability of colonization of unoccupied lek sites by greater prairie-chickens (Tympanuchus cupido L.) decreased to b 2% as the proportion of woodland increased N 20% (McNew et al, 2012). Lek sites of greater prairie-chickens in Minnesota, Wisconsin, and Kansas were negatively associated with forest landcover (Merrill et al, 1999;Niemuth, 2003;Gregory et al, 2011). Forest cover was cited as a strong predictor of greater prairie-chicken lek presence with mean percent forest cover two to three times greater at random points than at lek sites (Merrill et al, 1999;Niemuth, 2003); only 9% forest cover renders prairie unsuitable for greater prairie-chicken leks (Gregory et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The probability of colonization of unoccupied lek sites by greater prairie-chickens (Tympanuchus cupido L.) decreased to b 2% as the proportion of woodland increased N 20% (McNew et al, 2012). Lek sites of greater prairie-chickens in Minnesota, Wisconsin, and Kansas were negatively associated with forest landcover (Merrill et al, 1999;Niemuth, 2003;Gregory et al, 2011). Forest cover was cited as a strong predictor of greater prairie-chicken lek presence with mean percent forest cover two to three times greater at random points than at lek sites (Merrill et al, 1999;Niemuth, 2003); only 9% forest cover renders prairie unsuitable for greater prairie-chicken leks (Gregory et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Lek sites of greater prairie-chickens in Minnesota, Wisconsin, and Kansas were negatively associated with forest landcover (Merrill et al, 1999;Niemuth, 2003;Gregory et al, 2011). Forest cover was cited as a strong predictor of greater prairie-chicken lek presence with mean percent forest cover two to three times greater at random points than at lek sites (Merrill et al, 1999;Niemuth, 2003); only 9% forest cover renders prairie unsuitable for greater prairie-chicken leks (Gregory et al, 2011). Additionally, greater prairie-chickens select prairie for nesting where tree cover is minimal and nest survival increases as distance to nearest tree increases (McKee et al 1998;Matthews et al, 2013;Hovick et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…McKee et al (1998) found nest success decreased substantially when more than 5% woody cover was present at nest sites. Merrill et al (1999) found no traditional booming grounds within 1 mi (1.6 km) of any town or forest patch greater than 75 ac (30 ha), although Toepfer (STCP, personal communication) has since observed several booming grounds within 1 mi (1.6 km) of towns in the Merrill et al (1999) study area following a substantial GPC population increase.…”
Section: Habitat/ecosystemmentioning
confidence: 89%
“…Toepfer (1988) and Niemuth (2003Niemuth ( , 2005 found landscapes surrounding GPC booming grounds in Wisconsin contained more grass and less forest than unused random points. Similarly, Merrill et al (1999) found Minnesota booming grounds occurred in landscapes containing less residential farmstead, smaller amounts and smaller patches of forest, and greater amounts of Conservation Reserve Program (CRP) lands, which provide suitable grasslands for prairie-chickens (Toepfer 2003). Toepfer (2003) reported that increasing the treeless area from 140āˆ’540 acres (57-219 ha) around a Wisconsin booming ground by removal of scattered trees increased annual survival of cocks from this booming ground by at least 20% compared to males from control booming grounds.…”
Section: Habitat/ecosystemmentioning
confidence: 99%
See 1 more Smart Citation